Software Fault Prediction using Data Mining Techniques: A Survey - Kumar, Ashwni; Gupta, D.L. (International Journal of Computer Sciences and Engineering, 2019)
In recent studies, it is found that a fault prediction technique plays an important role especially in software development. Software fault prediction implies a decent investment in better style in future system to avoid building a fault prone modules. Faulty modules are expected using data mining techniques such as various classifiers which are used to classify faulty or non faulty modules. Many researchers have been produces different approaches for predicting fault in the software. In this paper it is found that various fault prediction techniques have been used and also found out the way to judge the performance of fault prediction methodologies in recent year. The main objective of survey is to identify best prediction techniques for detecting fault in early stage, and also determine the problem area in software fault prediction methodology which provides improvement in software development system. This paper presents the survey on fault prediction using data mining techniques which will helpful for further research in field of software fault prediction.